FC064: Histopathological and Clinical Outcomes of Anca Negative Versus Anca Positive Pauci-Immune Glomerulonephritis. (3rd May 2022) - Floyd, Lauren; Morris, Adam; Elsayed, Mohamed; Baksi, Ananya; Dhaygude, Ajay
Abstract: BACKGROUND: It has been suggested that pauci-immune small vessel vasculitis exhibits a different spectrum of disease in the absence of detectable circulating anti-neutrophil cytoplasmic autoantibodies (ANCA). This study aims to investigate the differences in clinical presentation, renal histopathological and clinical outcomes amongst vasculitis patients with or without detectable circulating ANCA. METHOD: A cohort study of biopsy proven pauci-immune glomerulonephritis was constructed from a single centre between 2006 and 2016 and followed up until June 2021. Patients were stratified by ANCA status at the time of diagnosis and primary outcomes compared the histopathological classification, clinical presentation and outcomes including mortality and end stage renal disease (ESRD) of those with ANCA negative and positive disease. Secondary outcomes looked at multivariate survival and logistic models comparing remission and relapse rates between the two groups. RESULTS: From 146 patients, 21.9% ( n  = 32) had ANCA negative disease with a male predominance of 66% ( n  = 21) and a younger mean age at diagnosis compared to those with positive ANCA serology; 51.44 ± 19.57 years versus 65.6 ± 12.10 years, respectively (P  ≤ 0.001). ANCA negative serology was associated with more renal limited disease ( n  = 20, 62.3% versus n  = 44, 38.6% ANCA positive) and the presence of extra-renal disease with ENT and constitutional symptoms occurred more frequently in ANCA positive patients (27% versus 0%; P = 0.0013). There was a comparable spread across the Berden classification, with no significant difference seen between the positive and negative groups (Table 1 ). The predominant class across both cohorts was focal classification. At the time of diagnosis, ANCA-negative patients had lower eGFR than those with positive ANCA serology (14.0 versus 18.0 mL/min/1.73 m 2 ; P = 0.09 922). At the end of follow-up, 53.1% ( n  = 17) of ANCA-negative patients had progressed to end stage renal disease (ESRD) which was higher than those with ANCA positivity ( n  = 13, 11.7%). When adjusting for age, sex and induction therapy, the hazard ratio (HR) for ESRD was five times higher in ANCA-negative patients compared to ANCA positive [HR 5.20 (2.02–13.39); P ≤ 0.001]. Mortality rates were higher in the ANCA-negative cohort (Figure 1 ). Following HR calculations and multivariate analysis, age was associated with a higher risk of death. In addition, despite the ANCA-negative cohort being younger, when adjusting for age, sex and induction therapy, the HR of death was three times higher in the ANCA-negative cohort [HR 3.0 (1.36–6.63); P = 0.007]. CONCLUSION: Our single-centre experience suggests that ANCA negative disease tends to occur in younger patients, with a higher rate of renal limited disease. Seronegative disease is less likely to relapse but is associated with a high mortality rate. The reasons for these differences between ANCA-positive and ANCA-negative cohorts are complex and multifaceted. Some reports hypothesize that the cause for severe disease at presentation in the absence of circulating ANCA is due to a delay in diagnosis and treatment by clinicians [1, 2 ]. This study provides the impetus for further trials looking at ANCA-negative and ANCA-positive disease.